Adaptation to macrophage killing by Talaromyces marneffei. (30th June 2017) - Pongpom, Monsicha; Vanittanakom, Pramote; Nimmanee, Panjaphorn; Cooper, Chester R; Vanittanakom, Nongnuch
Talaromyces ( Penicillium ) marneffei is an important opportunistic fungal pathogen. It causes disseminated infection in immunocompromised patients especially in Southeast Asian countries. The pathogenicity of T. marneffei depends on the ability of the fungus to survive the killing process and replicate inside the macrophage. Major stresses inside the phagosome of macrophages are heat, oxidative substances and nutrient deprivation. The coping strategies of this pathogen with these stresses are under investigation. This paper summarizes factors relating to the stress responses that contribute to the intracellular survival of T. marneffei . These include molecules in the MAP signal transduction cascade, heat shock proteins, antioxidant enzymes and enzymes responsible in nutrient retrieval. There is speculation that the ability of T. marneffei to withstand these defenses plays an important role in its pathogenicity. Lay abstract: Talaromyces marneffei is an important dimorphic fungus that causes disease in immunocompromised patients. The pathogenicity of T. marneffei depends on the ability of the fungus to survive the killing process and replicate inside the host macrophage cells. This paper summarizes factors relating to the stress responses that contribute to the intracellular survival of T. marneffei . There is speculation that the ability of T. marneffei to withstand these defenses plays an important role in its pathogenicity.